Penerapan Prototipe Mesin Pengisi Gelas Semi Otomatis untuk Efisiensi Air Minum Kemasan - Zainal Abidin Achmad; R. Ayu Firdausi Novira Rachman; Pungky Febi Arifianto; Zatin Niqotaini; Sjafiatul Mardliyah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
Saringembat Village, Singgahan District, Tuban Regency, faces the challenge of high-calcium groundwater quality, which contributes to high stunting rates. To address this issue, the UPN